Frequency of cytochrome P450 CYP2C9 variants in a Turkish population and functional relevance for phenytoin - Sükrü Aynacioglu, A (Blackwell Science Inc, 1999)
AIMS: The genetically polymorphic cytochrome P450 enzyme CYP2C9 metabolizes many important drugs. We studied the frequency of the amino acid variants cysteine(144) (CYP2C9*2) and leucine(359) (CYP2C9*3) in a Turkish population and the correlation between genotype and phenotype using phenytoin as probe drug. METHODS: CYP2C9 alleles *2 and *3 were measured in 499 unrelated Turkish subjects by PCR and restriction fragment length pattern analysis. Phenotyping was performed in a subgroup of 101 volunteers with a single oral dose of 300 mg phenytoin and concentration analysis in serum drawn 12 h after dosage. RESULTS: CYP2C9 allele frequencies in 499 unrelated Turkish subjects were 0.794 for CYP2C9*1, 0.106 for CYP2C9*2 and 0.100 for CYP2C9*3. Mean phenytoin serum concentrations at 12 h after dosage were 4.16 mg l(−1) (95% CI 3.86–4.46) in carriers of the genotype CYP2C9*1/1, 5.52 mg l(−1) (4.66–6.39) in CYP2C9*1/2, and 5.65 mg l(−1) (4.86–6.43) in CYP2C9*1/3. These differences were significant and accounted for 31% of total variability in phenytoin trough levels. Mean 12 h concentration ratios of 5-(para-hydroxyphenyl)-5-phenylhydantoin/phenytoin (p-HPPH/P) were 0.43 (0.39–0.47) for CYP2C9*1/1 compared with 0.26 (0.21–0.31) for CYP2C9*1/2, 0.14 (0.13–0.14) for CYP2C9*2/2, 0.21 (0.18–0.24) for CYP2C9*1/3, and 0.02 for CYP2C9*3/3; all mutant genotypes were significantly different compared with CYP2C9*1/1. CONCLUSIONS: Frequency of the two CYP2C9 variants in Turkish subjects was in a similar range as in other Caucasian populations. A significant proportion of the interindividual variability in phenytoin trough levels is explained by the genotypes. The 12 h serum concentrations after a single phenytoin dose may be used for routine phenotyping of CYP2C9 mediated metabolic clearance and the p-HPPH/P ratios may be even more sensitive indicators of CYP2C9 activity.